2003
DOI: 10.1086/375263
|View full text |Cite
|
Sign up to set email alerts
|

Shadowing-based Reliability Decay in Softened n -Body Simulations

Abstract: A shadow of a numerical solution to a chaotic system is an exact solution to the equations of motion that remains close to the numerical solution for a long time. In a collisionless n-body system, we know that particle motion is governed by the global potential rather than by interparticle interactions. As a result, the trajectory of each individual particle in the system is independently shadowable. It is thus meaningful to measure the number of particles that have shadowable trajectories as a function of tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…A resimulation of an object with higher resolution may not reproduce its structure in detail, but it can still be viewed as the result of evolution from a nearby set of initial conditions (e.g. Hayes 2003).…”
Section: A Convergence Study Of Subhalo Populationsmentioning
confidence: 99%
“…A resimulation of an object with higher resolution may not reproduce its structure in detail, but it can still be viewed as the result of evolution from a nearby set of initial conditions (e.g. Hayes 2003).…”
Section: A Convergence Study Of Subhalo Populationsmentioning
confidence: 99%
“…On the other hand, analytical estimations give severe limits on the reliability of N-body calculations. For instance, it was shown that the orbits of particles diverge exponentially with time from their original trajectories (Goodman et al 1993;Hayes 2003).…”
Section: Introductionmentioning
confidence: 99%
“…First, in a large system, the motion of particles is governed far more by the global potential than by the positions of nearby particles, 16 and second, individual particles appear to encounter glitches independently of one another. 36,38 These observations suggest that if one particle encounters a glitch, then it will have a negligible effect on the motion of the others, at least at first, because one errant particle does not appreciably change the global gravitational potential created by the ͑millions of͒ other particles. In fact, the global potential will remain substantially valid as long as most particles are on valid trajectories.…”
Section: Shadowing the Gravitational N-body Problemmentioning
confidence: 99%
“…Figure 2 plots this fraction of nonglitched ͑that is, shadowed͒ particles as a function of time for a set of parameters described more fully in Ref. 38. As Fig.…”
Section: Shadowing the Gravitational N-body Problemmentioning
confidence: 99%